Messengers of the people? : An analysis of representation and role orientations in the Irish Parliament - O'Sullivan, Mary-Clare (Trinity College (Dublin, Ireland). Department of Political Science, 2002)
The objective behind this dissertation is to increase academic understanding of the operation of Irish representative democracy, since there has been no similar systematic and contemporary study of Dail Eireann or its members. At a broader level, it contributes to the political science discipline by applying theories and models generated elsewhere to a political system unique in its institutional and cultural composition. It also differs from existing research in applying a broader conception of representation, viewing it not merely as one dimension of a representative’s role, but rather as a defining feature underpinning all elements of an MP’s functions and activities. I use Irish TDs as my unit of analysis and draw upon theories of representation, role theory and the rational actor perspective. Based on data from face-to face interviews conducted with TDs as well as a survey, census data and material from the parliamentary record, I investigate the relationship between institutional rules and constraints, and the attitudes and behaviour of representatives.
Keywords: Political Science, Ph.D.; Ph.D. Trinity College Dublin